Development Student's Worksheets Solid Curved Surface Based on Augmented Reality - Zuhadur Ra'is Ariono Putra; Atik Wintarti (Prodi Pendidikan matematika Universitas Islam Majapahit (UNIM), Mojokerto, Indonesia, 2021)
The purpose of this research was to develop a good quality LKPD based on three aspects, namely validity, practicality, and effectiveness. This study utilized AR technology and follows the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model to develop student’s worksheets on solid curved surface. LKPD and learning outcomes tests were each validated by six experts, consisting of three worksheet experts and three test instrument experts. The result of the development of this student’s worksheets had validity score of 3.66 > 3,25, that indicate very valid. The LKPD was practice due to the score are 3.46 for observing and 3.63 for the response that both were than 3,25 which means fulfilling pratical aspect. The average score of learning outcomes was 78, but some students have not pass the exam. In order to gain the effective aspects so that improvements were needed by adding HOTS-type exercises in the LKPD